The Effect of Welding Parameters to Mechanical and Physical Properties during Resistance Welding of Titanium Alloys - AB RAHMAN, AIDIL (IRC, 2020)
One of the most well-known manufacturing process is called the welding method and it can be separated to many types and categories depending on its application. Resistance Spot Welding (RSW) is commonly used method in the welding process due to the capability of the method to be used for high volume production to any types of pure metal and alloys such as aluminium, stainless steel and even titanium. Next, due to increase of demand in using titanium in many application such as high speed vehicles, aerospace and also medical makes the manufacturing process for the materials to be more efficient to comply with the request. However, titanium and/or titanium alloys are considered to be relatively expensive and also essentially more difficult to be fabricated by standard method compared to conventional metal and alloys